Značilnosti doživljanja sebe pri osebah po amputaciji roke - Horvat, Barbara (Rehabilitacija (Ljubljana), 2013)
Background: Self-concept is a useful explanatory construct because it includes the individuals perception of him/herself. Numerous factors affect the way of experiencing ourselves and change the quality of our lives. Reduced capacity of functioning is one of these factors. We focused on individuals after amputation of the upper limb. The aim of our study was to investigate whether their self-concept (specifically the body self-concept) differs from persons without amputation. We also expected the presence of defence mechanisms. Methods: The study included 28 individuals - 14 in each group. We tried to match the basic demographic variables in both groups. We applied two questionnaires: the Tennessee self-concept scale for measuring the self-concept, and the Amputee Body-Image Scale for assessing satisfaction with the prosthesis. An interview was held also with each of the participants. The data were collected from June 2012 to January 2013 in cooperation with the orthotics and prosthetics outpatient clinic at the University Rehabilitation Institute in Ljubljana. Paired-samples t-test was used for comparing the groups. Results: A statistically significant tendency toward making extreme responses was observed in the group of persons after amputation. The standardized (T) values of the row scoresof almost one half of the participants in this group indicate the presence of defensive behaviour and increase the likelihood of invalid results, which prevents further interpretations. Conclusion: The questionable validity of the questionnaire scores indicates significant problems in the process of coping with the situation after amputation of the upper limb, linked to the altered physical schema. Professional support would be welcome to facilitate the strategies of coping with a modified body schema and lifestyle (especially during the first five years after amputation).
Keywords: copping; defence mechanisms; Grief; mourning; obrambni varovalni mehanizmi; proces spoprijemanja; psihološke posledice; psychological consequences; samopodoba; Self Concept; žalovanje